Use of melatonin as an inhibitor of apoptotic process for cryopreservation of zebrafish (Danio rerio) embryos - P. L. Castro; A. L. J. Ferraz; J. G. Patil; R. P. Ribeiro (Brazilian Journal of Biology, 2021)
Abstract This study investigated the use of melatonin to arrest the effects of apoptosis in vitrified zebrafish (D. rerio) embryos. Dechorionated embryos at 22-24 somite-stage were divided (n = 60/treatment) into a non-vitrified (Control Group, 0 M melatonin) and vitrified treatments with 0 M (T1), 1 µM (T2) and 1 mM of melatonin (T3). For vitrified treatments, a solution methanol/propylene glycol based was used and the embryos stored in -196 °C for a week. After thaw, survival rate, scanning electron microscopy, expression of anti (bcl-2) and pro-apoptotic (bax/caspase-3) genes, reactive oxygen species (ROS) formation and DNA fragmentation analyses were performed. No live embryos were obtained from vitrified treatments, observing a rapid degeneration immediately after thawing, with the vitelline layer rupture and leakage of its content, followed by breakdown of epithelial cells and melanisation of the tissue. Regarding the apoptotic process, T3 had the highest relative gene expression, for the three genes (P < 0.05) furthermore, T2 had similar expression of pro-apoptotic genes to CG (P < 0.05). ROS formation revealed that CG presented lower percentage of embryo surface area affected (3.80 ± 0.40%) (P < 0.05), in contrast, no differences were found among the other groups. T1 was most significantly (P < 0.05) damaged by DNA fragmentation. The vitrified groups with melatonin had similar damage levels of CG (P > 0.05). The inclusion of 1 µM of melatonin in the vitrifying solution, countered the effects of apoptotic process in post-thaw embryos, suggesting its utility in cryopreserving fish embryos.